Increased Risk of Serious Bacterial Infections Due to Maternal Immunosuppression in HIV-Exposed Uninfected Infants in a European Country. (22nd July 2014) - Taron-Brocard, Clement; Le Chenadec, Jerome; Faye, Albert; Dollfus, Catherine; Goetghebuer, Tessa; Gajdos, Vincent; Labaune, Jean-Marc; Perilhou, Anais; Mandelbrot, Laurent; Blanche, Stephane; Warszawski, Josiane; Mandelbrot, Laurent; et al.
Abstract : The risk of serious bacterial infection in human immunodeficiency virus–exposed but uninfected infants is inverse to the mother's CD4 count. This association remains significant during the first year of life. Abstract: Background. Morbidity and mortality are higher among human immunodeficiency virus (HIV) exposed but uninfected (HEU) infants than unexposed infants, particularly if the mother had a low CD4 count. We investigated the possible association between maternal immune depression during pregnancy and the risk of infection in HEU infants in the national French Perinatal Cohort (EPF). Methods. All neonates, born alive, to HIV-1–infected women enrolled in the EPF between 2002 and 2010 were included. The primary outcome was the first serious (hospitalization or death) infection during the first year of life. The main exposure variable was maternal CD4 cell count near delivery. The Kaplan–Meier method and multivariate Cox models were applied, with the different types of infections managed as competing events. Results. Among 7638 HEU neonates, 699 had at least 1 serious infection (of which 159 were bacterial) with a Kaplan–Meier probability of 9.3% (95% confidence interval, 8.7–10.0) at 1 year. The risk of serious bacterial infection during the first year of life significantly increased with lower maternal CD4 cell count, before and after adjustment for maternal CD4 cell count <350 and 350–499 CD4/mm 3 (adjusted hazard ratio = 1.7 [1.2–2.6] and 1.2 [0.8–1.9], respectively; P = .03). This association mainly concerned infections involving encapsulated bacteria ( P = .03). The risk of serious viral infection was, by contrast, independent of the mother's CD4 cell count. Conclusions. Maternal CD4 count is significantly and specifically associated with the risk of serious infections with encapsulated bacteria in HEU infants.